The Imagined Body in the Sufi Thought - Djerrah, Wahiba (Milev Journal of Research and Studies, 2023)
The topic of the article deals with one of the phenomena that characterizes the Sufi discourse, which is the characteristic of fiction and its role in creating and representing images, on the basis that the mystical experience is a secular mental experience in which the imagination component played a major role in building and constructing meanings, in the way that it is characterized by coding and not direct in proposing and dealing with concepts. The focus here is on a basic approach drawn by the imagination component, which is the body, as the symbol of connection and separation in the mystical experience, as will be explained below.